Teaching patient safety in global health: lessons from the Duke Global Health Patient Safety Fellowship. Issue 1 (20th February 2019) - Johnston, Bria E; Lou-Meda, Randall; Mendez, Sindy; Frush, Karen; Milne, Judy; Fitzgerald, Tamara; Sexton, J Bryan; Rice, Henry
Abstract : Health systems in low-income and middle-income countries (LMICs) have a high burden of medical errors and complications, and the training of local experts in patient safety is critical to improve the quality of global healthcare. This analysis explores our experience with the Duke Global Health Patient Safety Fellowship, which is designed to train clinicians from LMICs in patient safety, quality improvement and infection control. This intensive fellowship of 3–4 weeks includes (1) didactic training in patient safety and quality improvement, (2) experiential training in patient safety operations, and (3) mentorship of fellows in their home institution as they lead local safety programmes. We have learnt several lessons from this programme, including the need to contextualise training to local needs and resources, and to focus training on building interdisciplinary patient safety teams. Implementation challenges include a lack of resources and data collection systems, and limited recognition of the role of safety in global health contexts. This report can serve as an operational guide for intensive training in patient safety that is contextualised to global health challenges.